2017
DOI: 10.22452/iojel.vol1no1.5
|View full text |Cite
|
Sign up to set email alerts
|

Instructional Leadership Practices in International Schools in Malaysia: A Case Study

Abstract: The ever-growing popularity of international schools in Malaysia opens

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
7
0
2
Order By: Relevance
“…The principals need to monitor teachers' instructional activities in the schools, solve problems and act promptly taking the right action (Velarde, 2017;Okorji, Igbokwe & Ezeugbor, 2016). The Blueprint 2012 stated that there should be an ongoing dialogue between the stakeholders about performance and its possible consequences.…”
Section: Discussionmentioning
confidence: 99%
“…The principals need to monitor teachers' instructional activities in the schools, solve problems and act promptly taking the right action (Velarde, 2017;Okorji, Igbokwe & Ezeugbor, 2016). The Blueprint 2012 stated that there should be an ongoing dialogue between the stakeholders about performance and its possible consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is observed that collegiality has more intense predictive power and is followed by developmental focus. It is evident that leadership does not solely rely on principals or head of departments, but also other teachers working in the subject departments practice leadership to support colleague teachers (Velarde, 2017). Hence, working with colleagues is the major aspect of teacher leadership to lead within and outside the classroom (Sinha & Hanuscin, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In Malaysian secondary schools, studies link high performance of students in examinations with principals who manifest traits that reflect instructional leadership ideals (Musa & Noor 2017;Suraya & Yunus 2012). In international schools in Malaysia, school leaders stress the significance of creating a clear vision and promoting a positive climate in a culturally diverse learning environment (Velarde, 2017). Moreover, Harris et al (2017) interviewed Malaysian primary school principals who were able to explain their functions and responsibilities as instructional leaders, particularly in terms of monitoring teaching and learning in their schools.…”
Section: Instructional Leadership In the Malaysian Settingmentioning
confidence: 99%